Examining the Electrochemical Impedance at Low States of Charge in Lithium- and Manganese-Rich Layered Transition-Metal Oxide Electrodes. Issue 7 (1st January 2015) - Gowda, Sanketh R.; Dees, Dennis W.; Jansen, Andrew N.; Gallagher, Kevin G.
Abstract : Lithium- and manganese-rich layered transition-metal oxide (LMR-NMC) intercalation electrodes are projected to enable batteries with high energy density and low costs for energy. However, implementation of LMR-NMC materials are challenged by life limiting mechanisms as well as less than desired rate performance. Here-in, we use electrochemical characterization of LMR-NMC electrodes to examine the large magnitude of impedance and the asymmetric polarization between charge and discharge at low states of charge (SOC). The area-specific impedance (ASI) of LMR-NMC displays a similar dependency as standard layered lithium metal oxides when compared as a function of voltage rather than SOC. Numerical physics-based modeling is used to analyze and simulate the potential response. The increasing and asymmetric behavior of the ASI in LMR-NMC at low SOC is suggested to be the result of the differing lithium diffusivities in the heterogeneous, nano-composite metal oxide material. Transport of lithium within LMR-NMC is governed by the relatively facile nickel- and cobalt-rich domains. Conversely, the mass transport within the lithium- and manganese-rich domains are characterized as comparatively sluggish. Lowering the stoichiometry of the lithium and manganese to achieve an optimal energy density at relevant discharge rates is suggested as a potentially viable path forward.